Tuberculosis abdominal: desafíos diagnósticos e implicancias clínicas en un hospital de referencia de la Ciudad Autónoma de Buenos Aires - Laura Svidler López; Lucas Matías Tomatis; Gabriela Liliana Sidra; Joseph Carlos Torres Guerrero; Rita Liliana Ofelia Pastore; Martín Jaume; Luciana Perez Mora (Revista Argentina de Coloproctología, 2026)
Background: Abdominal tuberculosis (ATB) is an uncommon extrapulmonary manifestation with a nonspecific presentation, which frequently delays diagnosis. Evidence in adult populations in Argentina remains limited. Objective: To describe clinical features, diagnostic delay, surgical requirements, and outcomes in patients with ATB, and to compare findings according to HIV status. Methods: We conducted a retrospective observational study of adult patients diagnosed with ATB between January 2017 and October 2025 at Hospital Juan A. Fernández. Diagnosis was confirmed by microbiological, molecular (Xpert® MTB/RIF), and/or histopathological methods. Results: Twelve patients were included (median age 34 years, IQR, 27–39); 58,3% were female and 58,3% were HIV-positive. The most common symptoms were abdominal pain (91,7%), anemia (83,3%), weight loss (67,7%), and fever (67,7%). Disease distribution was intestinal in 41,7%, anorectal in 41,7%, and peritoneal in 33,3%, with disseminated disease in 83,3%. A presumptive diagnosis of ATB was established in 50% of patients, whereas the remainder were initially misdiagnosed as acute inflammatory abdomen or malignancy. Overall, 58,3% required surgical intervention. An elevated postoperative complication rate (57.1%) was observed, with the need for reoperation in three patients. Diagnosis was confirmed by histopathology (100%), culture (91,7%), and Xpert® MTB/RIF (50%), with most patients having more than one positive diagnostic modality. The median diagnostic delay was 32 days (IQR, 21–44). HIV-negative patients required surgery more frequently than HIV-positive patients (100% vs. 28,6%; p = 0.03). Conclusions: Abdominal tuberculosis should be considered in the differential diagnosis of acute abdomen and anorectal disease in high-prevalence settings, particularly in patients with HIV coinfection. In this series, anorectal involvement was frequent, and HIV-positive patients required less surgical intervention, which may reflect a higher level of clinical suspicion and earlier diagnosis. The disease is associated with diagnostic delays and may require surgical management in complicated cases and, to a lesser extent, for diagnostic purposes. Postoperative outcomes may be complex, with a higher rate of complications. A high index of clinical suspicion and a multimodal, interdisciplinary approach, including rapid molecular methods, are essential to reduce diagnostic delays and improve outcomes.